Accuracy of a dual path platform (DPP) assay for the rapid point-of-care diagnosis of human leptospirosis. - Scott A Nabity; Guilherme S Ribeiro; Carolina Lessa Aquino; Daniele Takahashi; Alcinéia Oliveira Damião; André H O Gonçalves; Demócrito B Miranda-Filho; Rena Greenwald; Javan Esfandiari; Konstantin P Lyashchenko; Mitermayer G Reis; Marco A Medeiros; et al. (Public Library of Science (PLoS), 2012)
BACKGROUND:Diagnosis of leptospirosis by the gold standard serologic assay, the microscopic agglutination test (MAT), requires paired sera and is not widely available. We developed a rapid assay using immunodominant Leptospira immunoglobulin-like (Lig) proteins in a Dual Path Platform (DPP). This study aimed to evaluate the assay's diagnostic performance in the setting of urban transmission. METHODOLOGY:We determined test sensitivity using 446 acute and convalescent sera from MAT-confirmed case-patients with severe or mild leptospirosis in Brazil. We assessed test specificity using 677 sera from the following groups: healthy residents of a Brazilian slum with endemic transmission, febrile outpatients from the same slum, healthy blood donors, and patients with dengue, hepatitis A, and syphilis. Three operators independently interpreted visual results without knowing specimen status. RESULTS:The overall sensitivity for paired sera was 100% and 73% for severe and mild disease, respectively. In the acute phase, the assay achieved a sensitivity of 85% and 64% for severe and mild leptospirosis, respectively. Within seven days of illness onset, the assay achieved a sensitivity of 77% for severe disease and 60% for mild leptospirosis. Sensitivity of the DPP assay was similar to that for IgM-ELISA and increased with both duration of symptoms (chi-square regression P = 0.002) and agglutinating titer (Spearman ρ = 0.24, P<0.001). Specificity was ≥93% for dengue, hepatitis A, syphilis, febrile outpatients, and blood donors, while it was 86% for healthy slum residents. Inter-operator agreement ranged from very good to excellent (kappa: 0.82-0.94) and test-to-test reproducibility was also high (kappa: 0.89). CONCLUSIONS:The DPP assay performed acceptably well for diagnosis of severe acute clinical leptospirosis and can be easily implemented in hospitals and health posts where leptospirosis is a major public health problem. However, test accuracy may need improvement for mild disease and early stage leptospirosis, particularly in regions with high transmission.